REVITALIZANDO A CENA DO CENTRO HISTÓRICO: PROCESSO DE CRIAÇÃO CÊNICA. - PEREIRA, Abel Lopes (2018)
As a result of the experience accumulated by the Company Theater Workshop - COTEATRO during its 28 years of operation, the project Revitalizing the Scene of the Historical Center was held in its physical space located in the neighborhood of Praia Grande center of São Luís Maranhão. Thus, play and improvisational drama, capable of producing the production of an effective dramatic creation, were the means used in this analysis, as ways of a profitable practice in this model of theater teaching. Participants were led as subjects in the teaching process, from the development of the activities performed, using the descriptive research method with the study and analysis of the registry of these activities, in a non-formal education environment. The members were encouraged to act through the actions developed. The elements of theatrical language were apprehended progressively by the exercises conducted by an instructor. This allowed for an experiment of ample experimentation of the artistic making, conducted in a way that happened not only in pedagogical levels, but mainly as an activity that resulted in concrete aesthetic learning in the creation and presentation of micro scenes.